Gypsum Binder With Increased Water Resistance Derived From Membrane Water Desalination Waste - Valentin Romanovski; Dmitry Moskovskikh; Hongbin Tan; Kirill Kuskov; Sergey Volodko; Abayomi Adewale Akinwande; Rajiv Periakaruppan; Fanyue Kong; Xiaoling Ma; Feihua Yang; Maksim Kamarou (Engineering Reports)
ABSTRACT A method has been developed for separating a mixture of calcium, magnesium and sodium sulfates obtained through the interaction of sulfuric acid and waste from the water purification process generated by using membrane filters. The primary goal of this method is to extract gypsum and produce gypsum‐based binders. Patterns were identified regarding how various types, ratio and quantities of additives: blast furnace slag, granite screenings, portland cement, electric steel smelting slag affect the water‐gypsum ratio, strength properties, and water resistance of high‐strength gypsum binders. It was found that adding a single‐component additive specifically to enhance water resistance does not significantly impact these properties. Complex additives have been developed based on Portland cement, granulated blast furnace slag, electric furnace slag, expanded clay dust, and granite screenings of various fractions. These additives are designed to maximize the water resistance of high‐strength gypsum binder based on synthetic calcium sulfate dihydrate. As a result, the water resistance coefficient increased from 0.45 to 0.52. Additionally, a technological block diagram of the process has been proposed.